2012
DOI: 10.1136/bmj.e6572
|View full text |Cite
|
Sign up to set email alerts
|

Stop the silent misdiagnosis: patients' preferences matter

Abstract: Proton pump inhibitors (PPIs) are a class of medications used to suppress production of gastric acid, and indications for their use include the treatment of dyspepsia, gastroesophageal reflux disease, and gastric and duodenal ulcers. Proton pump inhibitors are also recommended for hospitalized patients in intensive care unit settings for prophylaxis of stress ulcers. In the short term, PPIs are quite effective at symptom relief and treatment of these acid-related conditions; however, no recommendations have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
405
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(430 citation statements)
references
References 15 publications
11
405
0
Order By: Relevance
“…As a consequence, we need guidelines on how and when individual biomarkers (or a combination of them) should and should not be used as they represent unnecessary costs, based on demographic, clinical, logistical and economical variables. The process of shared decision making [47] might also be considered as relevant in using biomarkers for the diagnosis of MCI due to AD. Last, the current survey was based on visually rating of amyloid-PET; we anticipate that quantitative measures of ligand uptake will be increasingly used in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, we need guidelines on how and when individual biomarkers (or a combination of them) should and should not be used as they represent unnecessary costs, based on demographic, clinical, logistical and economical variables. The process of shared decision making [47] might also be considered as relevant in using biomarkers for the diagnosis of MCI due to AD. Last, the current survey was based on visually rating of amyloid-PET; we anticipate that quantitative measures of ligand uptake will be increasingly used in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…Katz et al [17] reported that patients with lower levels of health literacy tend to ask fewer questions regarding aspects of medical care, but that study was limited in size and generalizability because most patients were black women. Asking questions and engaging in shared decision-making are important to limit the potential for misdiagnosis of patient preferences [28], particularly in hand surgery, where even with traumatic injuries (like distal biceps rupture, clavicle fracture, and distal radius fracture), treatment is discretionary, directed primarily at quality of life, and therefore is highly preference-sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…This focus could include some reflection on both the ethical and instrumental rationale for shared decision making-that it treats patients with respect, harnesses multiple stakeholders' perspectives and expertise, and is responsive to patient values. Co-creation could therefore be presented as central to ensuring that health care is effective and valuable in terms that matter to health professionals, patients, and other stakeholders [8]. There could also be some emphasis on the practices of shared decision making, including perhaps the communication challenges of working with patients who might resist taking an active role in decision making.…”
Section: Teaching and Enacting Co-creation In Medical Schoolsmentioning
confidence: 99%